A novel 4D volumetric M-mode ultrasound scanning technique for evaluation of intravascular volume and hemodynamic parameters - Sahil Patel; Emily Kao; Xu Wang; Kristyn Ringgold; Jeff Thiel; Nathan White; Shahram Aarabi; Daniel F. Leotta (WFUMB Ultrasound Open)
Introduction: We use a novel 4-dimensional (4D) volumetric M-mode (VMM) ultrasound (US) technique to assess intravascular volume by monitoring the inferior vena cava (IVC). The VMM method expands the spatial coverage of standard M-mode scanning (depth vs time) by including lateral image direction and adds transducer tilt to cover the region surrounding the IVC. Current ultrasound methods for volume assessment suffer from intra- and inter-operator variability. The VMM technique aims to address these limitations, aiding in early detection of hypovolemia/hemorrhage and guiding resuscitation. Methods/technical approach: The 4D VMM technique was used on animals that underwent a swine hemorrhagic shock protocol with fluid resuscitation. 2D ultrasound images obtained were formatted in a 3D volume to capture changes over time in vessel size with respiration and volume status. Planes were then extracted from the 3D volume at multiple lateral locations to find and track the IVC. The vessel walls were manually traced on vertical planes (depth vs. time) to determine mean IVC diameter and IVC collapsibility at each measurement time point in the shock/resuscitation protocol. Planes at constant depth (lateral vs. time) were selected to extract respiratory and cardiac cycle data. Results: Mean IVC diameter in the baseline phase was significantly greater than in the hemorrhage phase (p = 0.020). There was no significant different in mean IVC diameter between baseline and resuscitation (p = 0.064) or hemorrhage and resuscitation phases (p = 0.531). There was no statistically significant difference in mean collapsibility or ΔIVC diameter between protocol phases. The 4D VMM technique effectively measured heart and respiratory rates, consistent with monitored vitals. Conclusion: 4D VMM identified IVC changes corresponding to blood loss and resuscitation during hemorrhagic shock as well as heart/respiratory rates. This innovative approach holds promise in reducing operator variability and providing actionable information during treatment of shock.